2015
DOI: 10.1186/s12885-015-1839-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of inhibitors of apoptosis proteins (IAPs) and caspases in prostate cancer: caspase-3 forms and XIAP predict biochemical progression after radical prostatectomy

Abstract: BackgroundThe expression status of apoptotic regulators, such as caspases and inhibitors of apoptosis proteins (IAPs), could reflect the aggressiveness of tumors and, therefore, could be useful as prognostic markers. We explored the associations between tumor expression of caspases and IAPs and clinicopathological features of prostate cancer – clinical and pathological T stage, Gleason score, preoperative serum PSA levels, perineural invasion, lymph node involvement, surgical margin status and overall survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…As key factors, caspases are involved in the initiation and execution of apoptosis [19]. Caspase-3 is a type of executioner caspase, which can proteolyze a lot of substrates causing the death of cell [20], while its direct inhibitor, X-linked inhibitor of apoptosis protein (XIAP), can prevent cell from apoptosis by suppressing caspase cascade [21]. Thus, XIAP/caspase-3 pathway may play an important role in radiotherapy-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…As key factors, caspases are involved in the initiation and execution of apoptosis [19]. Caspase-3 is a type of executioner caspase, which can proteolyze a lot of substrates causing the death of cell [20], while its direct inhibitor, X-linked inhibitor of apoptosis protein (XIAP), can prevent cell from apoptosis by suppressing caspase cascade [21]. Thus, XIAP/caspase-3 pathway may play an important role in radiotherapy-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Survivin is largely undetectable in most normal, terminally differentiated tissues with notable exceptions of vascular endothelial or haematopoietic cells. [8][9][10] Moriai et al 11 recently showed that targeting survivin may overcome tamoxifen resistance in breast cancer cells. [8][9][10] Moriai et al 11 recently showed that targeting survivin may overcome tamoxifen resistance in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…3A). These results suggest that CD164 may modulate NHA progression by increasing cell proliferation, which is considered to be associated with a significant decrease in the Bax/Bcl2 ratio (22). Cell viability was significantly increased in NHA cells overexpressing CD164 when compared with the vector control at 24, 48 and 72 h following transfection (P<0.01, P<0.001 and P<0.001, respectively; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that the Bax/Bcl2 ratio is involved in the release of cytochrome c to the cytosol, resulting in caspase activation (21). In addition, overexpression of the anti-apoptotic Bcl2 protein protects cells from apoptosis induced by stimulants (22). The present study demonstrated that silencing of CD164 in U87 cells results in upregulation of cleaved caspase 3 and alters the Bax/Bcl2 ratio by increasing Bax and decreasing Bcl2 expression.…”
Section: Discussionmentioning
confidence: 99%